An Assessment of Peer Influence on Youth Involvement on Crime in Maiduguri Metropolitan Council - Abdullahi, Musa (2018)
Peer group influence on youth crime is largely an area of interaction physically and impersonally. Physically interaction can take place in a compound, wards, schools or other socially organised activities such as youth camps, football clubs or other game activities, boys scout, girls guide, man ‘o’ war and debating society etc and specifically to assess peer influence on youth involvement on crime in Maiduguri Metropolitan Council. And specifically to examine the demographic characteristics of youth in Maiduguri, assess whether peer have influence on youth involvement in crime in Maiduguri. The study reviewed relevant theories and in particular Differential Association Theory which explained that criminal behaviour is learnt through interaction with other individual in a process of communication. The data were obtained from primary and secondary sources which involved the use of questionnaires and review of relevant literatures. The study interviewed 180 respondents. The data were analysed using descriptive statistics. The findings revealed that most of the crimes committed are mostly by Males, so Males are prone to committing crime, and they are between the ages of 18 to 25years and have secondary or degree qualification. It also revealed that crime committed by youths were due to influence of bad friends and those youth were from large family size, and their parents don’t allow outsiders to discipline them and they are unemployed and have poor parental upbringing which characterised by poverty, homelessness and frustration among others. The study recommends that parents, government and community organisations could provide adequate jobs and enabling environments for business to thrive, as this will curb crime among the youth in Maiduguri Metropolis. Keywords: Assessment, Peer Influence, Youth Involvement and Criminal Behaviou